Exploring Madrasah Students Mathematics Literacy Ability - M. Imamuddin; Zulmuqim; Nana Sepriyanti (CV. AFDIFAL MAJU BERKAH, 2022)
This study aims to explore students' mathematics literacy ability and its contributing factors. This research was conducted at MTsN 2 Bukittinggi with 20 students of grade VIII as the subjects the study. The students were selected through random sampling. The instruments used in this research were test and interview. The based on the research results, information obtained: 1) Students are not used to working on questions that are different from the sample questions given by the teacher, 2) Students feel the problems used in the questions are more difficult than routine problems given by the teacher, 3) Students are accustomed and feel comfortable with the questions. which is applicable, and 4) Students are not familiar with the Islamic context used in the questions. The findings in this study reveal that students’ Mathematics literacy ability is in the low category, and this low ability is caused by: 1) the problems given in mathematics learning tend to be the routine problems and 2) the students get accustomed to answering applicative questions and are not used to using them in contextual use (especially in Islamic context)